Lithium Permeation through Thin Lithium–Silicon Films for Battery Applications Investigated by Neutron Reflectometry. Issue 12 (16th August 2016) - Strauß, Florian; Hüger, Erwin; Heitjans, Paul; Geue, Thomas; Stahn, Jochen; Schmidt, Harald
Abstract: In the ongoing search for new negative electrode materials for lithium‐ion batteries, amorphous silicon with a theoretical specific capacity of almost 4000 mA h g −1 is still one of the most promising candidates. In order to optimize cycling behavior, prelithiation of silicon is discussed as possible solution. Yet, little is known about kinetics in the Li‐Si system, especially with a low lithium content. Using neutron reflectometry as a tool, lithium permeation through amorphous Li x Si layers was probed during annealing. From the results a lithium permeability (diffusivity×solubility) of P =(3.3±0.9)×10 −21 m 2 s −1 is derived for Li x Si ( x ≈0.1), which is identical to that of pure amorphous silicon. Abstract : Lithium Permeation : The ionic transport of lithium ions in amorphous Li x Si is important when silicon is used as anode material in lithium‐ion batteries. By using a neutron‐reflectometry based technique, lithium permeation through thin Li x Si layers ( x =0.1) is determined by isotope exchange. The permeability does not deviate substantially from the value of pure amorphous silicon, because no lithium–silicon transport path is established.